2007
DOI: 10.1007/s00213-006-0660-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute and chronic antidepressant treatments on memory performance: a comparison between paroxetine and imipramine

Abstract: In contrast to the persistent harmful effects of imipramine, chronic treatment with paroxetine does not alter spatial working memory performance and appears to improve temporal order memory performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 46 publications
3
27
0
Order By: Relevance
“…and determined no impairment in combination with scopolamine. Our results are consistent with the results reported by Naudon et al, in which paroxetine did not impair memory in the radial arm maze test 62 . There are limited studies investigating the effect of SSRIs on learning and memory in certain brain regions such as the prefrontal cortex.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…and determined no impairment in combination with scopolamine. Our results are consistent with the results reported by Naudon et al, in which paroxetine did not impair memory in the radial arm maze test 62 . There are limited studies investigating the effect of SSRIs on learning and memory in certain brain regions such as the prefrontal cortex.…”
Section: Discussionsupporting
confidence: 94%
“…However, Kumar and Kullkarni suggested that fluoxetine did not exhibit any negative effect when administered alone, and furthermore reversed scopolamine-induced impairment in a passive avoidance task 26 . Chronically paroxetine-treated rats exhibited no negative effect on memory in the delayed spatial win-shift test, and it has been suggested that this effect of paroxetine was related to brain regions such as the hippocampus and prefrontal cortex, which play a critical role in memory 62 . These inconsistent results of SSRIs on memory may be due to the use of different models.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were pretreated with antagonists for 30 min before addition of agonist. Imipramine hydrochloride (10 mg/kg; Sigma) (Naudon et al, 2007) or vehicle was administered daily to rats by intraperitoneal injections for 21 d and tissue was collected 1 d after the last injection.…”
Section: Methodsmentioning
confidence: 99%
“…In the future, examining the effects of LY379268 on a TM task designed such that memory of the control animals is poor may reveal effects as previous results with object recognition have shown enhanced memory following LY379268 treatment (1 mg/kg) under such conditions [24]. Extending the delay between the sample trials and the test trial may produce a suitably poor TM in control rats [35].…”
Section: Discussionmentioning
confidence: 97%